Between Transnational Cooperation and Nationalism: The Little Entente of Women in Czechoslovakia. Issue 1 (1st June 2022) - Dudeková Kováčová, Gabriela
Abstract: Focusing on the involvement of feminist activist women from Czechoslovakia in the Little Entente of Women (LEW), this article examines the ideological and political limits of transnational cooperation within such an international organization, one that aimed to promote women's rights and pacifism in Central and Eastern Europe. The case of Czechoslovakia suggests that deep, ideological divisions between liberal feminist and conservative nationalist threads within the LEW's national branch seriously undermined efforts at unity and "global sisterhood" on the international level. It became possible to overcome ideological and political differences in the 1920s without questioning the very existence of the LEW. However, the antirevisionist political agenda of states involved in the LEW was a decisive factor in its reorganization. This article characterizes the rather limited impact of the LEW's activities in Czechoslovakia and presents new details on its reorganization in the 1930s.